Особливості формування та обліку власного капіталу на підприємствах різних організаційно-правових форм - Стригуль, Лариса Станіславівна; Панчеха, К. О. (НТУ "ХПІ", 2014)
У статті досліджено особливості формування та обліку складових власного капіталу. Дана загальна характеристика рахунків обліку власного капіталу. Визначено рівні нормативно- правового регулювання операцій з власним капіталом на підприємствах різної організаційно- правової форми відповідно до чинного законодавства.

This article explores the essence of the category of "equity" is defined as its component objects accounting. Reviewed level of legal regulation of accounting transactions with equity in enterprises of different legal forms in accordance with the current legislation of Ukraine. The features of accounting formation and movement of the share capital in business partnerships. Revealed that the current approach in developing and monitoring the components of equity eliminates value accounting and information provision and thus prevents rational organization of control over the accuracy and legality of the formation of equity, profit distribution in the relevant areas and funds. Study of the formation and registration of equity in Ukraine revealed regulations governing equity transactions have legal gaps and legal conflicts in its structure. Considering these features and guidance of accounting equity company in accordance with its legal form an important part of improving the method of accounting to facilitate rational accounting.
Features of the formation and registration of equity in enterprises of different organizational forms
Keywords: зареєстрований капітал; пайовий капітал; капітал в дооцінках; додатковий капітал; резервний капітал; нерозподілений прибуток; вилучений капітал; неоплачений капітал; equity; organizational and legal form of the company; registered capital; share capital; capital reserve; retained earnings; seized the capital; unpaid capital